Social support networks and well-being of disabled veterans: the dual roles of institutional support and peer trust - Zhang, Qiuyue; Wang, Yi; Lin, Yili; Cao, Yu; Guan, XiaoBin (Frontiers in Psychology, 2025)
IntroductionExisting studies have consistently demonstrated a positive association between social capital and subjective well-being; however, systematic evidence on this relationship among disabled veterans remains limited. This study investigates how structural social capital—captured by the breadth of social support networks—affects the subjective well-being of disabled veterans in China. It further examines the mediating roles of perceived effectiveness of government assistance (institutional resource utilization) and comrade trust (relational social capital), as well as the moderating role of policy awareness in shaping these relationships.MethodsA stratified sampling strategy was employed to collect survey data from 472 disabled veterans across multiple regions in China. Structural social capital was measured through the size and diversity of respondents’ social support networks. Ordered Logit regression models were used to estimate the effects, and mediation and moderation analyses were conducted to assess underlying mechanisms.ResultsFirst, broader social support networks were found to be significantly and positively associated with higher levels of subjective well-being. Second, both perceived government assistance effectiveness and comrade trust significantly mediated this relationship, reflecting the dual embeddedness of institutional and relational resources. Third, policy awareness moderated the association, indicating a marginal substitution effect between formal and informal capital. Finally, the positive effect of structural social capital was more pronounced among older veterans and those with less severe disabilities.DiscussionThe findings highlight a synergistic mechanism between institutional services and social network resources in enhancing disabled veterans’ well-being. Policy implications include strengthening social support networks, improving institutional responsiveness, and increasing policy awareness, while tailoring interventions by age and disability severity. Such measures can more effectively transform social capital into psychological well-being.